Research, Collaboration, Experimentation: Creating a Digital Scholarship Unit in an Academic Library Setting - Rousseau, Paulina; O'Brien, Elizabeth (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Changes in traditional approaches to scholarship prompt new possibilities for the convergence of digital collections and scholarly communication. To meet the changing needs of its users, the University of Toronto Scarborough Library began a Digital Scholarship unit. The poster will describe both the rationale and practical considerations for establishing this unit. Des changements dans l’approche traditionnelle à l’enseignement donne lieu à de nouvelles occasions pour la convergence des collections numériques et la communication savante. Pour répondre aux besoins changeants de ses usagers, la bibliothèque du campus de Scarborough de l’Université de Toronto a mis sur pied une unité d’enseignement numérique. L’affiche présente les raisons et les considérations pratiques ayant mené à la création de l’unité.